TINJAUAN TERHADAP PANDANGAN MASYARAKAT TERHADAP TRANSGENDER DALAM KONTEKS SOSIAL, AGAMA, HUKUM, DAN MEDIS BERBASIS BUKU PANDUAN - Rustian, Ihsan Harits; Oktaviano, Ahmad Rizal; Hadi, Sofian (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This research explores the complexity and diversity of the concepts of equality and diversity in the context of transgender individuals. Equality, both formal and substantive, is analyzed with reference to laws, norms, and the processes involved. Diversity, as a natural element in human life, encompasses differences in gender and gender identity. In the current situation, ambiguity regarding gender status gives rise to the phenomenon of transgender or transsexualism, where individuals experience a mismatch between their intrinsic gender identity and physical form. Society tends to respond to transgender individuals with negative views, creating stigmatization and social isolation. The study delves into the social, religious, legal, and medical perspectives on transgender individuals. While some view it as a violation of God's nature, the human rights perspective encourages the respect of human diversity. Using a qualitative method, the research presents descriptive analyses of literature data. The focus is on the negative impact and societal perceptions of transgender individuals, emphasizing the need for understanding and empathy. The Islamic perspective emphasizes the prohibition of gender change, while the conventional legal perspective highlights explicit regulatory deficiencies.